Wisata Kampung Lukis Berbasis Masyarakat dalam Meningkatkan Pola Hidup Bersih dan Kreatif (Studi Kasus Desa Panderejo Kabupaten Banyuwangi) - Fitah Jamaluddin; M. Dhiya'ul Haqq; Indah Erna; Novie Aurelia (Jurnal Al-Tatwir, 2021)
Reporting from WHO Global TB (Tuberculosis) in 2020, more than ten million people in this world suffer from TB. In Indonesia alone, 845,000 people are infected with TB disease. In Banyuwangi, TB sufferers reached 2,169 people. Panderejo Village, is one of the villages that can be considered as slums for many years in Banyuwangi. Besides caused by piles of garbage, 70 percent of the majority of its citizens are active smokers. After the change of management in Gagak Rimang Youth Association, at last the local youth who were assisted by the local community began to move to clean the village once a week and carry out activities to beautify Panderejo Village. The current study employs qualitative research method. The data collection techniques employed interviews, observation, and documentation. The objectives of this study are namely: 1) to determine the types and components of Kampung Lukis tourist attraction, 2) to determine the community development in Kampung Lukis tourist attraction, 3) to determine the supporting and inhibiting factors of Kampung Lukis tourist attraction. The results of this study are namely: 1) Kampung Lukis tourist attraction is a cultural tourism that fulfils 6 tourism components, 2) the community development carried out in Kampung Lukis tourist attraction is to have a free English language learning. Then there are also village women who are more active in exploring their talents in the culinary field whose food will then be sold on Saturdays or Sundays during the culinary bazaar. 3) The supporting factor are the awareness and willingness of the local community to develop Kampung Lukis and the present of governmental support. While the inhibiting factor is the Covid-19 pandemic which weakens the joints of the activities and the economy.